Utilization of Lapindo Mud as Raw Material for Ceramic Roof Tile by Varying Burning Temperature - Nuri, Wasir; Retno, Dyah Tri (Eksergi, 2015)
Lapindo mudflow issued a very large volume of mud. The mud flooded rice fields, residential and industrial area to date has not been stopped but the mud bursts untapped yet. Therefore, attempted use Lapindo mud very much it to be made tile. Sludge containing 55.4% silica oxide, alumina 16.1% and 8.9% iron with the composition of the possibility of mud can be created tile roof. Dried mud that has been mashed into the grain size of 80 mesh, then water added until plastic. Mud that has plastic printed with size 6 x 3 x 3 cm and then dried using ambient air. After the dried samples were burned using a furnace at temperatures varying from 500 to 900oC, after chilling the samples tested compressive strength, fracture modulus and water absorption. The results showed that the higher the combustion temperature obtained greater compressive strength and less water absorption. Most compressive strength is 142 kg/cm2and smallest water absorption is 0.06 g/cm2at a temperature of 900oC. At combustion temperatures of 500 to 700oC fracture modulus down from 72.78 to 41.81 kg/cm2 while at 700 to 900oC fracture modulus rose to 126.7 kg/cm2. The best results obtained on the combustion temperature at 800oC with fracture modulus 103.18 kg/cm2 and water absorption 0.08 g/cm2. These results satisfy roof tile as type I according SII.0027 UDC-81. 666.74.